Bioprocessing Of Bajra Straw Using Locally Isolated Aspergillus Niger Hd-6 For Endocellulase Production (Applied Biological Research, 2014)
Aspergillus niger strain HD-6, isolated from Anand, Gujarat  (India), was evaluated for endocellulase enzyme production  through solid state fermentation (SSF) using bajra straw as main  carbon source. Various cultural conditions such as temperature,  pH, moisture content, incubation period, nitrogen source, inoculum  age and size, etc. were standardized for optimum enzyme  production. Using 3 g bajra straw as sole carbon source maximum  endocellulase production from 96 hr old A. niger HD-6 was  achieved at pH 5.0, incubation temperature 28°C and moisture  content 65% after incubation for 4 days.
Keywords: Bajra straw; endocellulase; optimization; solid state fermentation